Extracorporeal membrane oxygenation as a salvage therapy for patients with severe primary graft dysfunction after heart transplant. Issue 5 (14th April 2019) - Jacob, Samuel; Lima, Brian; Gonzalez‐Stawinski, Gonzalo V.; El‐Sayed Ahmed, Magdy M.; Patel, Parag C.; Belli, Erol V.; Makey, Ian A.; Thomas, Mathew; Landolfo, Kevin; Landolfo, Carolyn; Leoni Moreno, Juan Carlos; Yip, Daniel S.; et al.
Abstract: Background: Severe primary graft dysfunction (PGD) is the leading cause of early death after heart transplant. Aim: To examine the outcomes of heart transplant recipients who received venoarterial extracorporeal membrane oxygenation (VA‐ECMO) for severe PGD. Methods: We reviewed electronic health records of adult patients who underwent heart transplant from November 2005 through June 2015. We defined severe PGD according to International Society for Heart and Lung Transplantation consensus statements. Results: Of 1030 heart transplant patients, 31 (3%) had severe PGD and required VA‐ECMO. The mean (range) age was 59 (43‐69) years. Fifteen patients (48%) underwent prior sternotomy and 10 (32%) received a left ventricular assist device as a bridge to transplant. Severe PGD manifested as failure to wean from cardiopulmonary bypass in 20 patients (65%) and as severe hemodynamic instability in the immediate postoperative period in 10 (32%), including cardiac arrest in 3 (10%). Twenty‐five patients (81%) were successfully weaned from VA‐ECMO, and 19 (61%) were discharged; the other 12 (39%) died. Conclusions: Although VA‐ECMO is a common method for providing mechanical circulatory support to patients with PGD, multicenter studies are needed to assess factors associated with successful outcomes and improved survival of these patients.